Affecting Public Support for Economic Policies: Evidence from a Survey Experiment about Rent Control in Germany - Mathias Dolls; Paul Schüle; Lisa Windsteiger (Center for Economic Studies and ifo Institute (CESifo), 2023)
We conduct a survey experiment among 18,000 respondents in Germany to examine the determinants of support for rent control policies. Highlighting undesirable price and supply effects lowers respondents' agreement with rent control, while pointing out that it can prevent displacement of low-income tenants increases agreement. However, while our treatments shift support for the policy into the hypothesized direction, the effect size decreases in misperceptions. Our results suggest that responsiveness to new information depends largely on prior beliefs, which affect perceived credibility and political neutrality of the received information. Mere information provision is therefore not sufficient to effectively alter policy views.
Keywords: D72; D83; D91; R21; R31; R38; P43; 330; rent control; efficiency; redistribution; survey experiment